2020
DOI: 10.3171/2020.4.spine20198
|View full text |Cite
|
Sign up to set email alerts
|

Anterior lumbar compared to oblique lumbar interbody approaches for multilevel fusions to the sacrum in adults with spinal deformity and degeneration

Abstract: OBJECTIVEIn adult spinal deformity and degenerative conditions of the spine, interbody fusion to the sacrum often is performed to enhance arthrodesis, induce lordosis, and alleviate stenosis. Anterior lumbar interbody fusion (ALIF) has traditionally been performed, but minimally invasive oblique lumbar interbody fusion (OLIF) may or may not cause less morbidity because less retraction of the abdominal viscera is required. The authors evaluated whether there was a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The mean age for the patients was 50.54 ± 6.05 years, 50% were males and 50% were females, and the mean duration of the symptoms was 34.44 ± 16.68 months. Xi et al 32 in ODI and VAS as well. 36 Kanno et al 19 , in a case report study in 2014, showed a successful improvement in a series of back pain and leg pain of 2 cases with spinal stenosis at levels L5/S1.…”
Section: Discussionmentioning
confidence: 93%
“…The mean age for the patients was 50.54 ± 6.05 years, 50% were males and 50% were females, and the mean duration of the symptoms was 34.44 ± 16.68 months. Xi et al 32 in ODI and VAS as well. 36 Kanno et al 19 , in a case report study in 2014, showed a successful improvement in a series of back pain and leg pain of 2 cases with spinal stenosis at levels L5/S1.…”
Section: Discussionmentioning
confidence: 93%
“…However, when approaching segments above L4 in ALIF, vessel injuries could be the greatest concern [ 18 ]. At L5/S1, there no significant difference in LL and patient-reported outcomes, whether choosing either ALIF or OLIF for correction [ 33 ]. Despite studies claiming the potential of OLIF at L5/S1 level, with promising outcomes, especially in obese patients when ALIF bears higher risk, we preferred to choose ALIF when encountering L5/S1 surgery due to its better visualization and the easier approach at this level [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALIF and OLIF are very useful techniques at LS junction for restoring lumbosacral lordosis, by allowing placement of larger lordotic cages. Xi et al 47 reported comparable segmental lordosis by using the ALIF and OLIF techniques. Anand et al 4 reiterated the importance of achieving maximal correction of SL at LS junction using multi-level OLIF, especially at L5-S1.…”
Section: Lif At Lumbo-sacral Junctionmentioning
confidence: 98%